Batik-Based Local Content Implementation for Cultural Heritage Transmission and Elementary Students' Creativity Development - Putri, Dyka Septiana; Azizah, Fayruz Syamyllya Hasna; Sabrata, Heru; Ummah, Fiena Saadatul (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to describe the implementation of batik-based local content learning as an innovation supporting cultural heritage transmission and the development of creativity among elementary school students. This study employed a qualitative descriptive approach conducted at SDN Nguri 2, Magetan Regency, involving fourth-grade students as research participants. Data were collected through observations, interviews, and documentation during three stages of activities: introducing batik and its cultural values, learning various batik-making techniques, and practicing hand-drawn batik based on students’ imagination and creativity. Data analysis utilized Miles and Huberman’s interactive model comprising data reduction, data display, and conclusion drawing. The findings revealed that batik-based local content activities enhanced students’ enthusiasm, active participation, and creativity in the learning process, demonstrated by diverse motif creation, creative color usage, and independent color-mixing. In addition, batik activities fostered character values such as patience, accuracy, responsibility, and appreciation for national cultural heritage. The study concludes that batik-based local content serves as an effective medium for cultural preservation, character development, and 21st-century skills development in elementary schools.